THE ROLE OF PSYCHOLOGICAL CAPITAL IN EXPLAINING STUDENT SATISFACTION: INTEGRATING LEARNING GOAL ORIENTATION, POSITIVE EMOTIONS, AND MENTAL HEALTH - Elfitra Azliyanti; Akmal Akmal; Tyara Dwi Putri (Jurnal Apresiasi Ekonomi, 2026)
Student satisfaction has become a critical indicator of higher education quality, particularly in the context of increasing psychological demands faced by university students. This study aims to examine the structural relationships among mental health, psychological capital, positive emotions, learning goal orientation, and student satisfaction. Using a quantitative research design, data were collected from 165 university students through a structured questionnaire. The constructs of mental health, psychological capital, positive emotions, learning goal orientation, and student satisfaction were measured using validated indicators. Data were analyzed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) to test the proposed research model and hypothesized relationships. The results demonstrate that learning goal orientation and positive emotions have significant positive effects on psychological capital. Psychological capital also shows a strong positive influence on mental health and student satisfaction. Furthermore, the mediation analysis confirms that psychological capital significantly mediates the relationship between learning goal orientation and student satisfaction. These findings highlight psychological capital as a central mechanism linking motivational, emotional, and mental health factors to student satisfaction. The study contributes to the higher education and positive psychology literature by providing an integrative model supported by empirical evidence. Practically, universities are encouraged to promote learning-oriented environments, enhance positive emotional experiences, and support students’ mental health to strengthen psychological capital and improve student satisfaction.